Study on dynamic expansion and β-carotene accumulation in storage root of orange-fleshed sweetpotato, and screening of germplasm resources with high rate of medium-sized storage roots - Ma, Guang-Yuan; Yan, Cai-Yue; Liu, Huilan; Chen, Yong-Xian; Zhao, Zi-Han; Tang, Dao-Bin; Zhang, Kai; Wang, Ji-Chun (Frontiers in Plant Science, 2026)
As an important food and economic crop, sweetpotato (Ipomoea batatas L.) has garnered widespread attention globally. Storage roots (SRs) of orange-fleshed sweetpotato (OFSP) varieties are rich in β-carotene, which holds significant importance for human health. The medium-sized SRs are popular in the market. However, germplasm resources with both high β-carotene content and medium-sized storage root rate (MSR) are severely lacking. This study analyzed SR expansion and β-carotene accumulation in six sweetpotato germplasm resources with varying β-carotene levels, and conducted a two-year dense planting field trial to boost MSR and screen elite OFSP germplasms with high β-carotene content, MSR and yield. Results revealed germplasm-specific differences in SR expansion and β-carotene accumulation. Among the tested germplasms, Qingyushu No.6, Yushu615 and Yuhongxinshu No.3 maintained stable β-carotene levels at about 9.09 mg/100g, 4.56 mg/100g and 11.54 mg/100g during growth, while Yuhongxinshu No.2 showed a zigzag rising trend from 4.99 mg/100g to 7.25 mg/100g. Over the two years of dense planting, Qingyushu No.6, Yushu615 and Yuhongxinshu 26 all achieved the MSR of over 70%, with the highest of 87.13%, indicating high MSR could be successfully obtained through dense planting strategy. Notably, superior germplasm, Yuhongxinshu 26, which simultaneously showed high β- carotene, MSR and yield, were successfully screened. These findings provide new insights into the physiological mechanisms and genetic potential of important traits in sweetpotato, offer theoretical support for optimizing cultivation practices, and lay theoretical and material foundations for breeding superior fresh-eating OFSP varieties with both high nutritional and commercial values.